Reforestation, carbon sequestration and agriculture: can carbon financing promote sustainable smallholder activities in Nicaragua? - Porras, Ina; Amrein, Alexandra; Vorley, Bill (2015)
This report explores the CommuniTree project that links forest activities in smallholder agriculture to carbon sequestration in Nicaragua. Managed by Taking Root, it is fully financed through the sale of carbon offsets. Farmers establish mixed-species forest plantations and receive a cash payment for ecosystem services (PES). The project currently involves 280 families and has issued over 250,000 carbon offsets certified by Plan Vivo. Plantation management also provides other sources of income, from sales of timber from the thinning process and expected future timber sales. Because they are part of agroforestry systems, trees help increase farm resilience and provide shade to other crops. The project also supports the promotion of additional market linkages, for example for sustainably produced forest products and tree nurseries, and provides local jobs for community members and local technicians. The project has kept transaction costs down by incorporating ICT tools into their systems. A strong marketing approach also keeps a steady inflow of carbon funding. CommuniTree’s successful approach is being explored for replication in Guatemala, Haiti and El Salvador, and its approach to data management and benefit sharing is informing the design of future Plan Vivo projects.